Lifelong learning – społeczno-kulturowe (re)konstrukcje - Melosik, Zbyszko (Studia Edukacyjne, 2018)
The article includes considerations on different version of lifelong learning in contemporary culture. Four approaches are analysed. The first one is classical, connected mostly with adult education,. In the second, lifelong learning is incorporated in neoliberal vision of man and society and is treated as a way of permanent change of one’s knowledge and skills to be competitive in a job market. Third approach relates to the role of popular culture in shaping man’s identity by developing ability to accept and quickly forget enormous numer of stimulus from mass media and consumption area. The core of last approach includes the conviction that just man’s passions are the best and deepest drive for permanent personal growth.